The optimal volume of a retention tank estimation using rainwater harvesting digital calculator - Napieraj, Paulina; Burszta-Adamiak, Ewa; Czarnocki, Piotr; Licznar, Paweł (Instal, 2024)
The increasing number of investments in the retention and use of rainwater in situ, in response to the ongoing climate change and extreme weather events, including primarily drought and heavy rainfall, as well as the significant supply of non-refundable funding from both domestic and foreign funds for such activities, is associated with the need for knowledge of methods and tools for reliable design and selection of the optimal volume of retention tanks. To date, there is a lack of standards and guidelines for in situ rainwater management in Poland. Using simplified methods to estimate tank capacity often results in significant discrepancies. This paper presents the selection of optimal retention tank volumes using a newly developed digital tool, the rainwater harvesting calculator on the WaterFolder platform, which takes into account both site conditions and precipitation conditions for a given region in the calculations. Demonstration calculations were carried out for 18 case studies (covering the three most common rainwater harvesting options, three locations and three runoff area sizes). The results showed that the selection of the optimal tank capacity is influenced not only by the size of the runoff area and the water demand for the chosen economic purposes, but also to a significant extent by the location, i.e., the local rainfall conditions in the area of the planned project. The use of such digital tools can streamline the design process and make it easier for developers to decide on the optimal capacity of a rainwater retention tank for on-site use.